ANALISIS STRATEGI PENGEMBANGAN KOPERASI DI KOTA MEDAN DENGAN METODE ANALISIS SWOT DAN ANALYTICAL HIERARCHY PROCESS (AHP) - Ali Sakti Hamonangan Nasution; Paidi Hidayat (Departemen Ekonomi Pembangunan USU, 2014)
Cooperative development is appropriate to the development of social. Cooperative identical with democratic economic systemis believed tobe an alternativeto solve socio economic problems in Indonesia. However, to date the cooperative movement in Indonesia is still more dominantas compared moral movement as the economic movement in concrete can improve the economic welfare of its members. Institutionally, the cooperative is more self effacing as a social vehicle when it should be the role of cooperatives is not just limited to social roles, but also roles in the economy. Cooperatives should be able to provide areal contribution to the economic empowerment of the people. Otherwise, the cooperative is expected to be a corner stone of the economy will collapse, driven by other economic act or sareprivate and state owned enterprises. In connection with this background, the research aimed to analyze the strategy of cooperative development in the city of Medan in 2014 by using the SWOT method and Analytical Hierarchy Process (AHP).Keywords : Cooperative Development Strategy, SWOT Analysis, Analytical Hierarchy